Transformasi Strategi Pembelajaran PAI di Era Society 5.0 Berbasis Rekonstruksionisme: Studi Kasus di SMA Negeri 1 Tuban - Muhammad Afiq Saifuddin; Moh. Mundzir; Lathifatul Aulia; Moch. Ikhwanudin (CV. Kalimasada Group, 2025)
The purpose of this study is to analyze the transformation of Islamic Religious Education Development Strategy (PAI) based on the philosophy of Reconstructionism in the context of society era 5.0. Reimagining is an educational philosophy that shapes the construction of educational systems to address social and technological challenges in modern society. This study uses a quantitative descriptive method that combines literature and case studies. The case study was conducted at SMA Negeri 1 Tuban through observation, interviews, and documentation of learning activities. The results showed that the PAI learning strategy in schools has undergone significant transformations: teachers work as facilitators, project-based learning and technology integration are carried out, and research is oriented towards high-level thinking skills (HOTS). These strategies are in line with the principles of Reconstructionism, which aims to develop students who are critical, creative, and have a strong Islamic character to face the digital era. Therefore, the philosophy of Reconstructionism becomes relevant and can be applied in changing the learning strategy of PAI in the era of Society 5.0.